Role of toll-like receptors gene polymorphism in hepatocellular carcinoma. (October 2014) - Lin, Wei; Chen, Jinkun; Zhu, Bo; Xu, Xiling; Dong, Zhiyong
Abstract Toll-like receptors (TLRs), evolutionarily conserved innate, play important roles in the development of autoimmunity. TLRs proteins are localized on the cell surface or in endosomes and play critical roles in innate immune responses against different pathogens. Aberrant stimulation of the innate immune system through intracellular TLRs may lead to hyperactive immune responses and contribute to the pathogenesis of hepatocellular carcinoma (HCC). HCC is the seventh most common cancer and the third leading cause of cancer deaths worldwide, and innate immune takes a most important role in HCC. There was no review to sum up the role of TLRs gene polymorphism in HCC. This review was performed to sum up the role of TLRs gene polymorphism in HCC.